Gangnam Style and Global Visual Culture. (2nd July 2016) - Shin, Ryan
Abstract : Global visual culture has emerged as a significant art-educational site and requires a critical examination of its characteristics and properties in relation to art education theory and practices. In this article, by analyzing the viral music video, Gangnam Style (2012), and its broad popular appeal, I discuss how global visual culture facilitated by social media and networking has become participatory, transnational, and cosmopolitan while providing critical foundations and implications for art educators to address a new global culture landscape in art education. I also argue for engaging students in global learning sites for cosmopolitan and participatory learning offered in and through social media and networking.